Well-being adjusted health expectancy - a new summary measure of population health - Magdalena Muszyńska-Spielauer; Marc Luy (Austrian Academy of Sciences (ÖAW), Vienna Institute of Demography (VID), 2021)
We propose a new summary measure of population health (SMPH) called well-being-adjusted healthy life expectancy (WAHE). WAHE belongs to a subgroup of health-adjusted life expectancy indicators and measures life expectancy equivalent to full health. The measure combines health and mortality information into a single indicator with weights that quantify the reduction in well-being associated with decreased health. WAHE's advantage over other common SMPHs lies in its ability to differentiate between the consequences of health limitations at various levels of severity and its transparent, simple valuation function. We also demonstrate that WAHE accounts for how health impairment impacts overall well-being according to selected individual and contextual factors. Our paper empirically evaluates WAHE's performance in terms of agreement and reliability, as well as how strongly it correlates with the other SMPHs when applied to 29 European countries. Health and well-being data are from the 2018 EUSILC, while life tables are from Eurostat. WAHE's sensitivity to univariate and multivariate state specifications is tested using three Minimum European Health Module health dimensions: chronic morbidity, activity limitations, and self-rated health. The findings show that WAHE has the highest and most significant correlation with all well-known SMPHs (health expectancy and disability-adjusted health expectancy from the Global Burden of Disease). Moreover, WAHE estimates are in agreement with all other SMPHs. Additionally, like the other SMPHs, all WAHE variants form a group of reliable indicators for studying population health in European countries. Finally, WAHE estimates are robust, regardless of whether health is defined across one or multiple simultaneous dimensions of health. We conclude that WAHE has several advantages over other standard SMPHs and propose adopting it as a universal health indicator for descriptive use in public health.
Keywords: 300; Health expectancy; health adjusted life expectancy; well-being; health; EU-SILC; well-being adjusted life expectancy; WAHE